2018
DOI: 10.18499/2225-7357-2018-7-1-14-26
|View full text |Cite
|
Sign up to set email alerts
|

The Participation of Mast Cells in Adaptation of the Stomach of Mongolian Gerbils to the Gravitational Factor

Abstract: Цель-изучить морфофункциональное состояние популяции тучных клеток (ТК) желудка монгольских песчанок после 12-суточного космического полета. Материал и методы. Эксперимент выполнен на 35 монгольских песчанках, 12 из которых находились в условиях 12-суточного космического полета на борту КА «Фотон-М» №3, 11 животных составили группу синхронного эксперимента, моделирующего некоторые условия орбитального полета, 12 особейвиварийную группу. Объект исследования-ТК фундального отдела желудка. Использованы гистохимич… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…For some tissues and animal species, an immunohistochemical reaction on c-kit was demonstrated to reveal mast cells better than toluidine blue [122], and not less effectively than tryptase immunohistochemistry [123]. However, other studies revealed that this marker is not sufficiently specific, and REVIEWS using antibodies to c-kit it is possible to image only a part of mast cells, which are immunopositive to tryptase or chymase [124,125], and vice versa, only a part of c-kit-immunoreactive cells were also immunopositive to tryptase or chymase [125]. This is due to the fact that c-kit receptor, in addition to mastocytes, is detected in stem and germinal cells, epithelial cells of sweat glands, ducts of the mammary gland, renal and testicular tubules, interstitial cells of Cajal, melanocytes, and basal cells of the epidermis, some neurons and gliocytes of the brain [126][127][128].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…For some tissues and animal species, an immunohistochemical reaction on c-kit was demonstrated to reveal mast cells better than toluidine blue [122], and not less effectively than tryptase immunohistochemistry [123]. However, other studies revealed that this marker is not sufficiently specific, and REVIEWS using antibodies to c-kit it is possible to image only a part of mast cells, which are immunopositive to tryptase or chymase [124,125], and vice versa, only a part of c-kit-immunoreactive cells were also immunopositive to tryptase or chymase [125]. This is due to the fact that c-kit receptor, in addition to mastocytes, is detected in stem and germinal cells, epithelial cells of sweat glands, ducts of the mammary gland, renal and testicular tubules, interstitial cells of Cajal, melanocytes, and basal cells of the epidermis, some neurons and gliocytes of the brain [126][127][128].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…This allows admitting the presence of either direct effects of cosmic radiation on the crosslinking of amino acids in collagen molecules, or the phenomena of disorganization of fibrous structures resulted from the developing trophic disorders. In addition, it is impossible to exclude the influence of matrix metalloproteinases, which can be actively functioning under conditions of gravitational unloading, including the influence of mast cell proteases [23][24][25]. In particular, the bioeffects of cosmic radiation were demonstrated in an experiment on a cultured human fibroblasts exposed for 14 days aboard the ISS [26].…”
Section: Discussionmentioning
confidence: 99%
“…A number of experimental studies allow assuming that the state of the intercellular substance of the connective tissue of various gastrointestinal organs after a space flight or under ground-based simulated physiological effects of weightlessness is closely related to the features of mast cell population [3,4,35]. Notably, the active secretion of proteases, tryptase and chymase, whicah are capable of activating matrix metalloproteinases and, as a result, accelerating the degradation of collagen fibers, seems to be especially important [18,21,[23][24][25]36]. The ability of mast cells to migrate in all layers of the walls of hollow organs and to actively secrete various factors determines their potential active participation in the gastric and intestinal stroma remodeling during space flight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation